Using the Social Skills Improvement System (SSiS) Rating Scales to assess social skills in youth with Down syndrome - Channell, Marie Moore; Mattie, Laura J.; Schworer, Emily K.; Fidler, Deborah J.; Esbensen, Anna J. (Frontiers in Psychology, 2023)
This study provides preliminary data on the Social Skills Improvement System (SSiS) Rating Scales Parent Form to measure social skills in a sample of 124 children and adolescents with Down syndrome (DS) ages 6-17 years. Overall, participants demonstrated relatively mild symptoms, with the sample’s average standard score falling within 1 standard deviation from the mean of the normative sample for the social skills (M = 92, SD = 15) and problem behaviors (M = 104, SD = 12) domains (normative sample M = 100, SD = 15 for both domains). However, a wide range of scores was observed across the sample for the composite and subscale scores. Differential patterns were also observed by subscale. For some subscales (i.e., Cooperation, Assertion, Responsibility, Engagement, Externalizing, Hyperactivity/Inattention, and Autism Spectrum) a disproportionate number of participants scored in the below average (i.e., lower levels of social skills) or above average (i.e., more symptomatic in problem behaviors or autism spectrum) range relative to the normative sample; for other subscales (i.e., Communication, Empathy, Self-Control, Bullying, and Internalizing), participants’ score distribution aligned more closely to that of the normative sample. SSiS composite scores correlated in the expected directions with standardized measures of autism characteristics, executive function, and expressive language. This study provides some of the first evidence validating the use of the SSiS in youth with DS, filling a gap in standardized measures of social functioning in this population.